Error reports in the light of error management climate, task complexity and personnel composition - Marco Haid; Sabine Graschitz; Peter Heimerl (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2019)
Purpose: This study examines the impact of error management climate, task complexity and personnel composition on the willingness to report errors in audit firms. A high willingness to report errors enables the proper conduction of an audit and is associated with higher organizational performance. Design/methodology/approach: We use a mixed-subject case-based experiment to gain data for the examination. A total of 53 certified Austrian and German auditors participated in the experiment. For the data analysis, we use descriptive statistics and nonparametric test procedures to investigate significant differences. Findings: The results indicate that a proper error management climate is the most important factor for the willingness to report errors, which increases under an 'error-tolerant' error management climate. The impact of the error management climate is independent of the task complexity and the personnel composition in which the error occurred. Research limitations/implications: The use of other methods and approaches to manipulate and operationalize the variables may lead to different results. Originality/value: This study contributes to the growing body of literature on error management climate. The analysis of the influence of task complexity and personnel composition on the willingness to report errors offers new insights into the impact and significance of error management climate in audit firms.
Keywords: M40; M42; 330; Error Management Climate; Personnel Composition; Error Report; Audit Quality; Task Complexity